Statistical Modeling of Egg Weight and Egg Dimensions in Commercial Layers - Abanikannda, O.T.F.; Olutogun, O.; Leigh, A.O.; Ajayi, L.A. (International Journal of Poultry Science, 2006)
Egg weight and dimensions of table eggs from Harco heavy breed layers in the humid tropics of Lagos, Nigeria were measured, and relationships between Egg Weight (EGGWT), Egg Length (EGGLT), Egg Width (EGGWD) and Egg Shape Index (SHPINDX) were studied. A total of 2951 eggs obtained from layers in five different age groups were sampled. Egg weight and egg width exhibited similar pattern in their distribution across the different age groups, with steady increase from age group A (22 - 32 weeks), peaked at age group D (55 - 65 weeks) before a decline afterwards. Egg length consistently increased with increasing age of hen, while shape index consistently decreased with increasing age of hen. Correlation between egg weight & egg length, egg width and shape index was 0.78, 0.84 and -0.07 respectively, while the correlation between egg length & egg width and shape index was 0.53 and -0.60 respectively, and between egg width and shape index was 0.37. The fitted model of the study was EGGWT = -124.72 + 1.65(EGGLT) + 1.32(EGGWD) + 0.43(SHPINDX). All coefficients obtained were significant (P< 0.05), however, it was observed that egg length and egg width were better predictors of egg weight when compared to shape index. Analysis of variance revealed that effects of all factors studied (age group, egg length, egg width, shape index and egg length x egg width interaction) were highly significant (P< 0.01) on egg weight except for shape index which was significant (P< 0.05). Egg dimensions were good estimators of egg weight.